A Recipe for Success, Necessary Dimensions of Operations Management: A Case Study based on Walmart's Triumphs - Trung Ngo Minh; Vananh Phamthi; Duc Ngo Minh (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
Purpose: This paper aims to analyse operations management's importance in three main dimensions: having a successful strategy, an efficient supply chain management system, and continuous innovation. The case of Walmart is used to consolidate these three areas. The main methodology of this paper is quantitative. The previous empirical literature on operations management and Walmart will be utilized to assess three important areas of operations management that are relevant for business today. Findings: The results indicate that strategy, supply chain management, and innovation play an important role in effective operations management. Particularly, the research on Walmart has shown that a low-price policy (EDLP) strategy, streamlined supply chain management by constructing communication and relationship networks with suppliers, and routine innovation have enabled Walmart's success. Limitations: The research only focuses on three operations management areas. Moreover, this research paper only studies Walmart's case. Thus, its findings may not be generalizable unless more case studies can be analyzed.
Keywords: O32; O33; M11; 330; Strategy; innovation; SCM